PENGARUH BELANJA MODAL, INVESTASI, DAN PRODUK DOMESTIK REGIONAL BRUTO TERHADAP PENDAPATAN ASLI DAERAH - Theodora Ririn; Rida Prihatni; Yunika Murdayanti (Fakultas Ekonomi, Universitas Negeri Jakarta, 2014)
This research aims to examine the effect of capital expenditure, investment, gross domestic regional product toward the local original income at all provinces in Indonesia the period 2010-2012. Factors tested in this research were capital expenditure, investment, gross domestic regional product as independent variables whereas local original income as dependent one. The data was a secondary one and numbers of sample used in this research is ninety (90) local governments which is has been passed the purposive sampling used by researcher. From the data collected, then processed and analyzed using multiple regression analysis with 0.05 standard significance rate. The simultaneous result showed that the three of independent variables significantly effected the dependent one which was local original income. On the other side, partial result showed that there’s not significant the effect of capital expenditure toward the local original income. And there’s an positive significant influence between investment, gross domestic regional product toward the local original income. Keywords: capital expenditure, investment, gross domestic regional product, local original income.